THE ROLE OF DERBENT IN THE DEVELOPMENT OF RUSSIAN-PERSIAN TRADE IN THE XVII CENTURY - Magomedov, Nazim Abdurahmanovic; Magaramov, Sarafetdin Arifovic (History, Archeology and Ethnography of the Caucasus, 2015)
The article is devoted to the study of the role of Derbent as a transit hub in the implementation of trade and economic contacts between Moscow State and Persia in the 17th century. Based on the analysis of written sources and archival data, the trade turnover of the eastern merchants of Derbent, their activities to involve the city in the orbit of Russian eastern trade are shown. The data on the role of Derbent merchants proper in expanding the city’s trade contacts with the outside world are given. The work clarifies the reasons for the interest of the Russian government and Persia in mutual trade, carried out through the south-western Caspian region. The study shows that Derbent served as a transit hub and a transit point in Russian-Persian trade of the 17th century.